BATS INDICATORS OF DISTURBED HABITATS IN THE ALLPAHUAYO MISHANA NATIONAL RESERVE, PERUVIAN AMAZON - RAMOS RODRÍGUEZ, María Claudia (2018)
We consider that the changes in the composition of bat species in the face of anthropic impacts, could show its potential in terms of indicator species. Therefore, identify these species in disturbed habitats using bats has become the purpose of this study. We applied the mist network method for 20 nights in two types of habitats in the Allpahuayo Mishana National Reserve: Disturbed forests, corresponding to crops and natural forests without alteration. During each night, 16 mist nets were installed, active from 18:00 to 24:00 hours and reviewed every 30 minutes. We captured 451 individuals that corresponded to 37 species applying an effort of 1936 h/net. We recorded species indicating disturbed forests (p=0.0003), the most noteworthy being Sturnira tildae, followed by Carollia perspicillata, Sturnira lilium, Carollia brevicauda and Carollia benkeithi. The most abundant species in both types of forests was Artibeus planirostris and probably the most important in the natural regeneration processes of the forests studied. According to the food guild, the greatest wealth and abundance of frugivorous bats is found in disturbed forests (p=0.001). According to the results, the bats constitute a good taxonomic group to be applied in the method of states of conservation of biodiversity in Amazonian forests; which would be attractive and generate an impact of ecological, economic, social and scientific cost benefit.